Placenta-on-a-chip: a novel platform to study the biology of the human placenta. (2nd April 2016) - Lee, Ji Soo; Romero, Roberto; Han, Yu Mi; Kim, Hee Chan; Kim, Chong Jai; Hong, Joon-Seok; Huh, Dongeun
Abstract: Objective : Studying the biology of the human placenta represents a major experimental challenge. Although conventional cell culture techniques have been used to study different types of placenta-derived cells, current in vitro models have limitations in recapitulating organ-specific structure and key physiological functions of the placenta. Here we demonstrate that it is possible to leverage microfluidic and microfabrication technologies to develop a microengineered biomimetic model that replicates the architecture and function of the placenta. Materials and methods : A "Placenta-on-a-Chip" microdevice was created by using a set of soft elastomer-based microfabrication techniques known as soft lithography. This microsystem consisted of two polydimethylsiloxane (PDMS) microfluidic channels separated by a thin extracellular matrix (ECM) membrane. To reproduce the placental barrier in this model, human trophoblasts (JEG-3) and human umbilical vein endothelial cells (HUVECs) were seeded onto the opposite sides of the ECM membrane and cultured under dynamic flow conditions to form confluent epithelial and endothelial layers in close apposition. We tested the physiological function of the microengineered placental barrier by measuring glucose transport across the trophoblast-endothelial interface over time. The permeability of the barrier study was analyzed and compared to that obtained from acellular devices and additional control groups that contained epithelial or endothelial layers alone. Results : Our microfluidic cell culture system provided a tightly controlled fluidic environment conducive to the proliferation and maintenance of JEG-3 trophoblasts and HUVECs on the ECM scaffold. Prolonged culture in this model produced confluent cellular monolayers on the intervening membrane that together formed the placental barrier. This in viv o-like microarchitecture was also critical for creating a physiologically relevant effective barrier to glucose transport. Quantitative investigation of barrier function was conducted by calculating permeability coefficients and metabolic rates in varying conditions of barrier structure. The rates of glucose transport and metabolism were consistent with previously reported in vivo observations. Conclusion : The "Placenta-on-a-Chip" microdevice described herein provides new opportunities to simulate and analyze critical physiological responses of the placental barrier. This system may be used to address the major limitations of existing placenta model systems and serve to enable research platforms for reproductive biology and medicine.